Pertanggungjawaban Pidana Pelaku Tindak Pidana Illegal Fishing (Studi Kasus Putusan Pengadilan Negeri Tanjung Pinang Nomor 32/Pid.Sus- PRK/2020/Pn Tpg) - Pakpahan, Marlina Elisabeth; Simbolon, Leonard; Andika, Andika (Universitas Medan Area, 2025)
This article aims to analyze the criminal liability of perpetrators of illegal fishing based on the Decision of the Tanjungpinang District Court Number 32/Pid.Sus-PRK/2020/PN Tpg. The focus lies on law enforcement efforts, the form of criminal responsibility, and the judge’s legal considerations regarding violations committed by the foreign vessel’s captain operating without an official fishing permit. The analysis applies the theoretical framework of criminal liability and maritime law. Data were collected through document studies of statutory regulations and court decisions, and analyzed qualitatively. This study concludes that criminal liability in this case was imposed in the form of a fine and confiscation of evidence due to jurisdictional limitations under UNCLOS. Although no custodial sentence was issued, the judge exercised a cautious and proportionate legal approach that aligned with national and international law, making the decision a significant precedent for fisheries law enforcement in Indonesia.